Garlic (Allium sativum L.) polysaccharide ameliorates type 2 diabetes mellitus (T2DM) via the regulation of hepatic glycogen metabolism - Chanyuan Xie; Wei Gao; Xue Li; Shuangshuang Luo; Di Wu; Fook, Yee Chye (Elsevier GmbH, 2023)
This study intends to explore the antihyperglycemic effect and the possible hypoglycemic mechanism of garlic (Allium sativum L.) polysaccharide (GP) using an animal model. Kunming mice were fed with GP (1.25, 2.5, 5.0 g/kg‧bw) for five weeks after insulin resistance (IR) engendering by a high-oil-high-sugar diet and streptozotocin (STZ). Intragastric administration of GP effectively improved the disease of polyphagia and polydipsia in diabetic mice. The fasting blood glucose (FBG) in the high-dose GP (DGH) group was meaningfully 42% lower than that in the diabetic model (DC) group showing its hypoglycemic effect. GP might manipulate hepatic glycogen metabolism by regulating the content of glucokinase (GK), glycogen synthase (GS), and phosphoenolpyruvate carboxykinase (PEPCK). Results showed that GP with a low relative molecular weight (MW) of 2.0 kDa consisted predominately of a 2,1-β-D-Fruf backbone with 20.7% side chains owning the structure-effect on hypoglycemia indicating it could be a potential supplement for the intervention and management of hyperglycemia.